Differences in the rotational properties of multiple stellar populations in M13: a faster rotation for the ‘extreme’ chemical subpopulation - Cordero, Maria J. (Monthly notices of the Royal Astronomical Society, 2016)
We use radial velocities from spectra of giants obtained with the WIYN telescope, coupled with existing chemical abundance measurements of Na and O for the same stars, to probe the presence of kinematic differences among the multiple populations of the globular cluster (GC) M13. To characterize the kinematics of various chemical subsamples, we introduce a method using Bayesian inference along with a Markov chain Monte Carlo algorithm to fit a six-parameter kinematic model (including rotation) to these subsamples. We find that the so-called extreme population (Na-enhanced and extremely O-depleted) exhibits faster rotation around the centre of the cluster than the other cluster stars, in particular, when compared with the dominant ‘intermediate’ population (moderately Na-enhanced and O-depleted). The most likely difference between the rotational amplitude of this extreme population and that of the intermediate population is found to be ∼4 km s−1 , with a 98.4 per cent probability that the rotational amplitude of the extreme population is larger than that of the intermediate population. We argue that the observed difference in rotational amplitudes, obtained when splitting subsamples according to their chemistry, is not a product of the long-term dynamical evolution of the cluster, but more likely a surviving feature imprinted early in the formation history of this GC and its multiple populations. We also find an agreement (within uncertainties) in the inferred position angle of the rotation axis of the different subpopulations considered. We discuss the constraints that these results may place on various formation scenarios.